PENGARUH KEBUGARAN JASMANI TERHADAP LAMA PERSALINAN KALA I DAN II PERSALINAN PADA IBU PRIMIGRAVIDADI BPM KOTA MEDAN TAHUN 2015 - Bangun, Sartini; Hutabarat, Julietta; Gultom, Lusiana (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2015)
Physical fitness of pregnant women who are exercise actively have a better vascularization than those who passively. Physical exercise is a major factor in improving physical fitness, flow capacity of the heart, and obtain a high oxygen during labor (Varney and others 2007, Hamilton 1995, Bobak and others 2005), therefore team authors were interested in researching about physical fitness effectiveness for a long period time in first and second stage of labor in primigravida. Method : this type of research is a Quasi Experiment and Non-Equivalent Control Group, population total are 40 respondents (3rd trimester primigravida) measuring the level of physical fitness (VO max), period of 1st stage,  2nd   stage  and  total  period  time  of  labor.  Data  analysis  using  T  test.  Result  :  from    20 respondents of experimental group and 20 groups non-experiment obtained homogeneous data regarding physical fitness and psychological condition. The average time period of 1st stage in experimental group are 387,75 minutes (Sd. 43,54), the average time period of 2nd stage are 27,75 minutes (Sd. 9,66). Total period of labor average 334,50 minutes (Sd. 44,35), while in non- experimental group the period time of 1st stage average 448,75 minutes (Sd. 41,64), 2nd stage 40,00 minutes (Sd. 8,27) and the average of total period are 478,75 minutes (Sd. 82,64). T test in the experimental group and non-experimental group obtained homogeneous data because p value (0,794) > α (0,005). Period time of 2nd stage p value (0,602) > α (0,005). The period time of labor not normal, analysist using Mann Whitney test obtained p value (0,00) < α (0,005). Concluded that there is the influence of maternal physical fitness with period of 1st  and 2nd  stage of labor and suggested for all pregnant women improving physical fitness with physical exercise using a bicycle ergometer.